Optimum design and operation of a pump-piping-storage system. (1st January 2001) - Kaplan, H.; Seireg, A.; Dolen, M.
The study reported in this paper is undertaken to develop a computer simulation and an optimum design and operation strategy for a general storage system. The influence of various design parameters on the total operation cost of the system for a general delivery regime is also studied. The computer program which incorporates a general procedure for the design and control of the pump-piping-storage system is presented. The main considerations in the reported study are the worst-case storage capacity analysis and the allowance for variations in the friction factors. The computer model of the system is applicable to any of pump-piping-storage system with appropriate changes in some of the system parameters. Two important parameters of the system are the average standby and operation times. The solution of the cost optimisation problem is undertaken using non-linear programming.